Kesalahan Berbahasa Bidang Linguistik pada Pidato Mahasiswa MPBI-UMS yang Berperan sebagai Bupati Terpilih Boyolali - Wiwik Ariesta; Atiqa Sabardila (Literasi : Jurnal Bahasa dan Sastra Indonesia serta Pembelajarannya, 2021)
One of the language skills related to the speaking aspect is speech. Speeches are usually made by leaders or people who have important roles, such as the regent or mayor. Even giving a speech is not without errors or obstacles, especially the use of words or sentences that are spoken, causing confusion, misunderstanding, and even deviations. This study aims to describe the forms of language errors at several levels, including the fields of phonology, morphology, syntax, and spelling. The method in this study is a qualitative descriptive method. The data is taken from Indonesian language errors in the speeches of MPBI-UMS students. The collection technique uses recording, note-taking, and observation techniques. Data analysis is done by grouping the data based on the error category. The results of this study describe four areas of language errors, namely (1) phonological errors, including errors in the use of capital letters, the use of italics, and errors in number symbols; (2) morphological errors, including errors due to pleonasm and the use of prefixes; (3) syntax errors consist of errors in the use of redundant words, unclear sentences, and sentence composition; and (4) spelling errors, consisting of punctuation errors, use of non-standard words, and use of prepositions.